2009
DOI: 10.1016/j.neuropharm.2009.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of D2 and D3 dopamine receptor selective compounds on l-dopa-dependent abnormal involuntary movements in rats

Abstract: A panel of novel D2 and D3 dopamine receptor selective antagonists, partial agonists and full agonists have been evaluated for the ability to attenuate L-dopa associated abnormal involuntary movements (AIMs) in 6-hydroxydopamine (6-OHDA) unilaterally lesioned male Sprague Dawley rats, which is an animal model of L-dopa-induced dyskinesia (LID). LID is often observed in patients with Parkinson’s Disease following chronic treatment with L-dopa. The intrinsic activity of these dopaminergic compounds was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 62 publications
(84 reference statements)
5
59
1
Order By: Relevance
“…22,31 Development of D2 and D3 receptor subtype selective compounds would provide the pharmacological tools to enable the neuroscience community to better understand the role of these two receptor subtypes in complex behavioral and physiological processes. Furthermore, D2-like receptor subtype selective compounds of varying intrinsic activity have the potential for development of (a) pharmacotherapeutic agents for the treatment of neurological disorders, 6 neuropsychiatric disease, 32 and psychostimulant abuse, 33 and (b) neuroimaging agents to study the differential expression and regulation of D2-like dopamine receptors. 34,35 We initially assumed that ligand binding selectivity would be achieved by developing compounds capable of exploiting differences in contact residues between these two structurally related receptor subtypes.…”
Section: ■ Discussionmentioning
confidence: 99%
“…22,31 Development of D2 and D3 receptor subtype selective compounds would provide the pharmacological tools to enable the neuroscience community to better understand the role of these two receptor subtypes in complex behavioral and physiological processes. Furthermore, D2-like receptor subtype selective compounds of varying intrinsic activity have the potential for development of (a) pharmacotherapeutic agents for the treatment of neurological disorders, 6 neuropsychiatric disease, 32 and psychostimulant abuse, 33 and (b) neuroimaging agents to study the differential expression and regulation of D2-like dopamine receptors. 34,35 We initially assumed that ligand binding selectivity would be achieved by developing compounds capable of exploiting differences in contact residues between these two structurally related receptor subtypes.…”
Section: ■ Discussionmentioning
confidence: 99%
“…For example, we have used SV 293 to investigate the utility of using D2-like receptor-selective antagonists for attenuating L -dopa-dependent abnormal involuntary movements in unilaterally lesioned animals, which is a rodent model of L -dopa-induced dyskinesia, a common side effect associated with the chronic administration of L -dopa in individuals with Parkinson's disease [5]. In those studies we reported that while D3 receptor-selective compounds attenuated abnormal involuntary movement scores, SV 293, at a dose of 10 mg/kg, exhibited only marginal activity.…”
Section: Resultsmentioning
confidence: 99%
“…These neuronal systems are involved in movement coordination, cognition, emotion, affect, memory and the regulation of prolactin secretion by the pituitary. Alterations in the dopaminergic pathways are thought to be involved in the pathogenesis of neurological, neuropsychiatric and hormonal disorders, including Parkinson's disease, schizophrenia and hyperprolactinemia [1,2,3,4,5,6]. In addition, modulation of the dopaminergic pathways is thought to occur as a consequence of acute and chronic abuse of pyschostimulants, including cocaine and amphetamines [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported on the development of a series of arylamide phenylpiperazines that have high affinity for D3Rs, moderate D3R:D2R binding selectivity (i.e., 23-51-fold), and low log P values (2.9-3.5) (Chu et al, 2005;Kumar et al, 2009). We found that three of these compounds-WC10, WC26, and WC44-reduced cocaine self-administration (Cheung et al, 2012).…”
Section: Introductionmentioning
confidence: 93%
“…Systemic cocaine, OS-3-106, WW-III-55, and their vehicles were given intraperitoneally, and 7-OH-DPAT and its vehicle were given subcutaneously. OS-3-106 and WW-III-55 were injected 5 minutes before the start of the test session, based on our previous study showing that arylamide phenylpiperazines attenuated L-DOPAinduced dyskinesia (Kumar et al, 2009) and reduced locomotor activity (Cheung et al, 2012) within this time frame.…”
Section: Evaluation Of the Effects Of Os-3-106 And Ww-iii-55 On Behaviormentioning
confidence: 99%